Odpowiedzi

2010-04-11T12:44:52+02:00
C) 6[1/4x-2]=18
3/2x-12=18
3/2x=18+12
3/2x=30//1,5
x=20
d) x/6-1/6=1/*6
x-1=6
x=6+1
x=7
e) -2[2x-1]=x/3
-4x+2=x/3/*3
-12x+6=x
-12x-x=-6
-13x=-6//-13
x=6/13
f) 2/5[3-x]=-2/*5
2[3-x]=-10
6-2x=-10
-2x=-6-10
-2x=-16
x=1/8
g) 3/4[2-3x]=-6/*4
3[2-3x]=-24
6-9x=-24
-9x=-6-24//-9
x= 3i1/9
h) 1/5[x-3]=9-x/*5
1x-3=45-5x
1x+5x=45+3
6x=48//6
x=8

prosze ; p



45 3 45
2010-04-11T12:46:57+02:00
C) 6(1/4x-2) =18
6/4x-12=18
6/4x=12+18
6/4x=30÷6/4
x=30×4/6
x=120/6
x=20
f) 2/5(3-x) = -2
6/5-2/5x=-2
3x=-2÷3
x=-2/3
g) 3/4(2-3x) = -6
6/4-9/4x=-6
-3/4x=-6÷(-3/4)
x=-6×(-4/3)
x=24/3
x=8
h) 1/5(x-3)=9 - x
1/5x-3/5=9-x
1/5x+x=3+9
1 1/5x=12÷7/5
x=12×5/7
x=60/7
x=8 4/7
20 3 20